Improving Narrative Writing Skills of Madrasah Tsanawiyah Students Through a Group Inquiry Learning Model Based on Religious Character Values - Mimi Mulyani; Sukron Mazid; Farikah Farikah; Dwi Riyanti; Atsani Wulansari (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
This research analyzes the effectiveness of the group inquiry learning model based on religious character values in enhancing narrative writing skills, specifically in the form of diaries. The objective is to evaluate how this model integrates Islamic religious education with literacy culture while fostering religious character values in the learning process. Employing a quasi-experimental method with a matching-only pretest-posttest control group design, the study was conducted with 76 eighth-grade students from Madrasah Tsanawiyah Negeri in Magelang City, Central Java, Indonesia. Data were collected through observations, interviews, and tests assessing narrative writing that incorporated religious character values such as siddiq, amanah, tabligh, and fathanah. The results revealed that the experimental group, which used the group inquiry model, showed significant improvements in writing skills (t-count = 3.081, sig. = 0.018). The N-Gain for the experimental group was 22.33, compared to 0.52 for the control group, demonstrating the model’s effectiveness. This research underscores the importance of integrating group inquiry learning with religious character values, as it significantly improves narrative writing skills, enhances student engagement, and instills core Islamic values, thereby contributing to the development of both literacy and character education in Islamic schools.